Metajournalistic discourse on media freedom in online media in Serbia - Mitrović, Marta; Vujović, Marija; Vulić, Tatjana (Sociološki pregled, 2024)
Metajournalistic discourse is a broad field of research, and its analysis provides insight into how different journalistic concepts are defined and legitimised within the profession. However, in addition to journalistic actors, numerous non-media actors also participate in the construction of metadiscourse in journalism. This paper analyses metajournalistic discourse (Carlson, 2016) on media freedom, with the aim of answering the following research questions: “Which actors build metadiscourse around the concept of media freedom in Serbia?” and “What is the tone of this metadiscourse?” As many as 674 texts collected during 2021 and 2022 from 10 online media outlets were analysed. The results of this analysis show that the metadiscourse on media freedom is mostly built by non-journalistic actors, while the most common tone of that discourse is critical. By cross-referencing the actors with the tone of discourse, it was concluded that a critical tone prevailed among all actors, both journalists and non-journalists, with the exception of state officials. They are also the only actors with a positive tone of discourse.
Keywords: metajournalistic discourse; media freedom; textual analysis; journalism